Incidence of water scarcity: understanding the triggers and implications for women’s non-agricultural livelihoods in Northern Ghana - Joseph Alhassan; Divine Odame Appiah; Suale Iddrisu; Andrews Ofosu; Josephine Tetteh (Cogent Social Sciences, 2024)
Water scarcity has multiple negative repercussions for women across the world due to their gender role in sourcing and collecting water for household uses. While this is the case, the triggers of water scarcity and its implications for women’s non-agricultural livelihoods in the East and West Mamprusi municipalities of northern Ghana are poorly understood in the literature. Guided by the feminist political ecology approach, and drawing on a triangulation mixed-method, involving a survey of 394 women, focus group discussions, and complemented with temperature data, this paper contributes to the body of knowledge by examining the triggers of water scarcity and its implications for women’s non-agricultural livelihoods in northern Ghana. Findings revealed that although residents have limited water points, with some of them being unsafe for drinking, a combination of physical and human factors are adding woes to their water shortage. Again, women were found to be suffering unduly from the water shortages with multiple adverse repercussions for their non-agricultural livelihoods. These findings highlight not only the need for local governments to step up efforts in water provision, but also recognize the gendered effects of water shortage in the East and West Mamprusi municipalities of northern Ghana.